Senkaku/Diaoyu Island Dispute and the Reconstruction of China as Japan’s “Other” - Kolmaš, Michal (Animo Repository, 2017)
In the recent years, much has been written about Japan’s security “normalization,” that is, the resurgence of Japan as a “proactive contributor to world peace.” This article aims to add to this debate, but it will approach it from a novel angle. Basing its epistemology in critical security studies, I investigate the relationship between national identity and Japan’s foreign policy (i.e., its normalization). The article dismisses realist assumptions that Japan’s security rejuvenation is a reaction to the changing balance of power in Asia. Rather, it argues that the normalization is a product of Japan’s discursive practice of victimization, that is, situating itself as a victim of foreign pressure. The identity of a victim is reproduced through the practice of “othering”—differentiating from various “others.” For most parts of the 20th century, the United States served as the focal other to Japan’s self-identification. In the last two decades, however, Japan’s identity has become practiced through differentiation to China. The article illustrates this process on the case study of Japan’s primary discourse on the Senkaku/ Diaoyu island dispute of 2010 through 2014. Japan’s narrative on the dispute has managed to depict China as a coercive, immoral and abnormal state that bullies subsequently weak, coerced, but moral and lawful Japan. By writing Japan as a coerced, yet lawful state protecting the status quo, Tokyo succeeded in persuading the United States to subdue the disputed territory under its nuclear umbrella. Through the process of victimization of a weak Japan then, the Prime Minister Abe Shinzo managed to propagate the new security legislature as a means of reconstruction of Japan from weak to a normal state.